Invasive Exploitation and the Multiplicative Hypothesis: Polyvictimization and Adolescent Depression Symptoms in Nepal - Emery, Clifton R. (Journal of interpersonal violence, 2022)
Adverse effects of childhood maltreatment experience and adolescent depression symptoms are theorized to be more profound for adolescents who have suffered multiple maltreatments (polyvictimization). New theoretical insights into the study of polyvictimization suggest that it must be studied using a multiplicative logic, particularly when maltreatment is characterized by invasive exploitation. This study, for the first time, examined the concept of invasive exploitation in the context of polyvictimization and its association with adolescent depression symptoms. The study used a random, three stage probability proportional to size (PPS) cluster sample of 565 mother-adolescent dyads in Kathmandu, Nepal, and also examined the protective effects of maternal empathy. We hypothesized that (a) singly, the empirical categories of maltreatment (neglect, physical abuse, and child sexual abuse) would associate positively with adolescent depressive symptoms and (b) main effects held constant, the interaction effects of a child sexual abuse X neglect and a child sexual abuse X physical abuse would be positive. Regression with clustering corrections found that neglect (B = 3.17, p < .01) and sexual abuse (B = 3.48, p < .05) positively associated with adolescent depression symptoms. Results support the multiplicative invasive exploitation polyvictimization hypothesis (child sexual abuse X neglect interaction; B = 6.14, p < .05). The positive neglect X sexual abuse interaction is consistent with the theory that sexual abuse is distinct as invasive exploitation, and demonstrates that the multiplicative hypothesis can be fruitfully applied to the study of polyvictimization. Interventions targeting polyvictims with experience of invasive exploitation and studies aiming to provide deeper insights into sexual abuse as invasive exploitation are needed.